Santri Youtuber: Development of Economic Independence of Youtube-Based Pesantren (Study of Al Hikmah Islamic Boarding School, Purworejo) - Najanuddin; Muhammad Januar Isdiyantoro (Journal of Islamic History, 2023)
This research aims to explain the economic empowerment of Pesantren Al Hikmah Purworejo through the YouTube platform and analyse the supporting and inhibiting factors. The research questions include: (1) How does Pesantren Al Hikmah in Purworejo develop and empower its economic independence through YouTube? (2) What are the supporting and inhibiting factors in the development and empowerment of the economic independence of YouTube-based pesantren in Al Hikmah, Purworejo? (3) How is the solution to overcome the obstacles in developing the economic independence of YouTube-based pesantren in PP. Al Hikmah, Purworejo? This research uses a qualitative approach with an in-depth case study design. The results showed that Pesantren Al Hikmah developed economic independence and empowerment through a model of approaches, strategies and techniques of pesantren management. The figure of the caregiver who has a fairly mature background experience in the world of YouTube, pesantren policies based on modern video production management, strategies and techniques for making videos based on the talents and interests of students become the basis for empowerment and independence of pesantren. There are several supporting factors, such as the background of many students from information technology vocational schools, students who take courses with IT majors, consistency in uploading videos and the ability to optimise videos based on YouTube algorithms. The inhibiting factors include the increasing competition, YouTube algorithms changing rapidly, taking video footage from external parties that contain copyright risks. To overcome these obstacles, PP. Al Hikmah, Purworejo has made a breakthrough by innovating the existing content, such as adding shades of horror and mystic nuances in each of the latest content, adding more video animations to avoid copyright reprimands, always consistently uploading videos at the same time according to recommendations from YouTube and always learning the types of changes in YouTube algorithms that always experience adjustments.   REFERENCES   Adek Media Roza, d. (2019). Seribu Wa Jah Pesantren Pondok Pesantren Tak Hanya Mengajarkan Agama, Tapi Juga Bisnis Dan Menjadi Pelopor Pemberdayaan Masyarakat. Jakarta: Tempo Publishing. Alawi, A. (2014). Mendidik tanpa Pamrih; Kisah para Pejuang Pendidikan Islam. Jakarta: Dirjen Pendidikan Islam. Dewantara, K. H. (1928 ). Sistim Pondok dan Asrama itulah Sistem Nasional. Wasita. Wasita, Jilid 1 No 2-Nopember. Fukuyama, M. (2018). Society 5.0: Aiming for a New Human-Centered Society. Japan spotlight, 47. Krisdamarjati, Y. A. (2021, (2021). Mari Berdayakan Media Sosial dengan Baik. Jakarta: Kompas.). Mari Berdayakan Media Sosial dengan Baik. Jakarta: Kompas. Retrieved from Kompas. Mihardja, A. K. (2008). Polemik Kebudayaan; Pergulatan Pemikiran Terbesar dalam Sejarah kebangsaan Indonesia. Jakarta: Balai Pustaka. Syahab, A. (2019). Al-Allamah Muhammad Hasyim Asy'ari Wadli'u Istiqlali Indonesia; H.Hasyim Asyari Pejuang Kemerdekaan Republik Indonesia. Jombang: Pustaka Tabuereng . Hasan Baharun (2021) Modernisasi Pendidikan di Pondok Pesantren: Studi tentang Pemanfaatan Sistem Aplikasi Pedatren dalam Meningkatkan Mutu Layanan Pondok Pesantren, Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, Vol. 6, No. 1 Juni. Izzatul Maghfiroh1 dan Arief Hidayat (2021), Sistem Informasi Perpustakaan Pesantren menggunakan Framework Laravel (Studi Kasus Pada Pondok Pesantren Luhur Wahid Hasyim Semarang, Jurnal Informatika dan Rpl, Vol. 3, No. 1, Maret 2021, Hal. 68-73. Nurul Qomariah Dkk (2021) dengan judul, Pengembangan Aplikasi Pengelolaan Pondok Pesantren berbasis Web, Studi Kasus: Pondok Pesantren Nurul Islam Mojokerto, Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputere, Vol. 5, No. 11, November, hlm. 4885-4891. Ulul Aedidan Asep Amaludin (2022), Modernisasi Sistem Manajemen Pesantren Dengan SIAP (Sistem Informasi Administrasi Pesantren) Pada Pondok Pesantren Sirojuth Tholibin, Journal Of Islamic Management Vol.2, No.2,Juli. Saifudin Zuhri, L. M. (2023, Desember 2023 Sabtu, 02). Pemilihan Topik Youtube. (Najanuddin, Interviewer) LIna. (2023, November Sabtu ). Kebijakan tentang Pesantren Youtuber. (Najanuddin, Interviewer) Lina. (2023, 10 2). Pengalaman Menjadi Santri Youtuber. (Najanuddin, Interviewer) Maqin, N. d. (2023, November Sabtu ). Kebijakan Pesantren Youtuber . (Najanuddin, Interviewer) Mihardja, A. K. (2008). Polemik Kebudayaan; Pergulatan Pemikiran Terbesar dalam Sejarah kebangsaan Indonesia. Jakarta: Balai Pustaka. Mujib, A. (2026). Ilmu Pendidikan Islam. Jakarta : Kencana Penada Media. Risalah, M. ( edisi 81/tahun XII/1439/Maret 2018 ). Laporan Utama, Para Kiai yang Wartawan . Jakarta: Majalah Risalah Nahdlatul Ulama. Risalah, M. ( edisi 87/tahun XII/1440/Oktober 2018). Dedikasi Santri Untuk Indonesia Mandiri. Jakarta : Majalah Risalah Nahdlatul Ulama . Syahab, A. (2019). Al-Allamah Muhammad Hasyim Asy'ari Wadli'u Istiqlali Indonesia; H.Hasyim Asyari Pejuang Kemerdekaan Republik Indonesia. Jombang: Pustaka Tabuereng . Tafsir, A. (1992). Ilmu Pendidikan dalam Perspektif Islam. Bandung : Remaja Rosdakarya. Ulama, R. N. (2019). Majalah Risalah Nahdlatul Ulama, Edisi 100/tahun XIII/1441 H/November/2019. Jakarta: Majalah Risalah Nahdlatul Ulama. Ulama, R. N. (edisi 87/tahun XII/1440/Oktober 2018). KH. Saaid Aqil Siroj: Dedikasi Tak Lekang Waktu . Jakarta: Majalah Risalah Nahdlatul Ulama. Zuhri, H. S. (2023, November Sabtu 18 November 2023). Pemberdayaan Pesantren Youtuber. (Najanuddin, Interviewer) Zuhri, H. S. (2023, November Sabtu 11 November 2023). Sejarah Perkembangan Pesantren Al Hikmah . (Najanuddin, Interviewer)